How Practice of Peer Assisted Learning Facilitates Better Learning among the Dental Students of Bangladesh - Rahman, ABM Rizwanur; Faruque, Mohammad; Alam, Kazi Khairul; Tasnim, Sanjida; Azeez, Mezbah Ul (Bangladesh Journal of Medical Education, 2018)
Peer assisted learning (PAL) is a common feature of medical education. PAL in the clinical setting, a complex learning environment, requires fresh evaluation. Socio-cultural theory is proposed as a means to understand educational interventions in ways that are practical and meaningful. This descriptive type of cross sectional study entitled practice of peer assisted learning among students in selected undergraduate dental colleges of Bangladesh was conducted in four Government and four non-Government dental colleges. The objective of this study was to explore the views of teachers and students regarding the benefits of practicing peer assisted learning. Sample size was 437 (407 students and 30 teachers). Data was collected from students with a self-administered semi-structured questionnaire and from dental teachers with indepth interview schedule. Data was analyzed by using SPSS 19. Most of the students opined that PAL method increased their knowledge. In the study most of the teacher said that PAL increased the confidence of the students and enhanced the conception about the topics. Teachers also said PAL developed good behavior of the students and also developed helping approach to others. This study finding showed that PAL method was very effective in higher education courses. So we should encourage the students and the teachers about the method. Bangladesh Journal of Medical Education Vol.9(2) 2018: 16-18